Therapeutic Benefits Of Commercially Available Gourd Family In Improvement and Sustainability of Human Health - Mohd Ab Azid, Saffanah; Wan Ishak, Wan Rosli (Universiti Sains Malaysia, 2018)
Cucurbit family are a fruit producing plants with 130 genera and 800 species and it is one of the genetically discrete groups of food plants such as pumpkin, cucumber, squash, gourd and melon. Cucurbit family provide an important dietary fibre, β-carotene (pro-vitamin A), potassium and vitamin C. Consuming dietary fibre regularly can prevent diabetes mellitus, obesity and cardiovascular disease. Pumpkin (cucurbita maxima) is widely cooked as desserts in Malay cuisines. 60-80% content of polysaccharides in pumpkin pulp func-tions as anti-tumour, anti-diabetic, hypolipidemic, and immune-stimulating activities. Winter melon (Benincasa hispida) is a source of water soluble polysaccharides, vitamin C while the taste is pleasant, sub acid and aromatic juicy flesh; a great source of functional food production and can be stored up a year. Rockmelon (Cucumis melo L) has nutritional value namely carbohydrates, ascorbic acid, folic acid and potassium while the seeds are rich in oil and protein, and the compounds of this fruit are functioning to prevent cancer, fighting depression, dandruff, ulcers and stimulate the immune system. The red flesh of watermelon (Citrulus lanatus) has anti-carcinogenic compounds. Cucurbit fruits have blood glucose lowering properties and the active ingredient has been